A novel fluorescent endoplasmic reticulum marker for super‐resolution imaging in live cells. Issue 5 (1st February 2023) - Han, Kai; Huang, Shuhan; Kong, Jie; Yang, Yang; Shi, Lei; Ci, Yali
Abstract : Endoplasmic reticulum (ER) is a highly complicated and dynamic organelle that actively changes its shape and communicates with other organelles. Visualization of ER in live cells is of great importance to understand cellular activities. Here, we designed a novel ER marker, RR‐mNeonGreen, which comprised an N‐terminal ER retention signal, a bright fluorescent protein (mNeonGreen), and a C‐terminal transmembrane region. Colocalization of RR‐mNeonGreen with mCherry‐KDEL verified that RR‐mNeonGreen perfectly labeled the ER. RR‐mNeonGreen showed better continuity of ER tubules when imaged by super‐resolution microscopy. Moreover, RR‐mNeonGreen is competent for live‐cell imaging of ER dynamics and tracing of the interaction between ER and mitochondria at high spatiotemporal resolution. In summary, RR‐mNeonGreen is a novel ER marker for super‐resolution live‐cell imaging with multiple merits. Abstract : This study constructs a novel endoplasmic reticulum (ER) marker, RR‐mNeonGreen, which is brighter and displays finer and more continuous ER networks. Using RR‐mNeonGreen, we successfully imaged ER dynamics in live cells and reconstructed the 3D structure of ER networks by structured illumination microscopy and stimulated emission depletion microscopy. Our novel ER marker is competent for super‐resolution imaging to study ER structures and dynamics.